Pengaruh Gaya Kepemimpinan, Pengembangan Karir dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Perusahaan Daerah Air Minum Kota Malang) - Ahmad Nurdin; Abdul Qodir Djaelani; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT The purpose of this research were to determine the affect of leadership style to the employee performance, career development to the employee performance, and work environment to the employee performance. Population in this research is all employees of Perusahaan Daerah Air Minum Kota Malang. The sample in this study amounted to 47 employees. Methods of this research was a quisionare and documentation. Data were analyzed by instrument test, classical assumption test, multiple linier regression and t-test. The result showed that the leadership style does not affect the perfromance of employees of. Career development affect the performance of employees. Working environment does not affect the performance of employees. Keywords: leadership style, career development, working environment, and perfomance of employees